Activation-inducible CAR expression enables precise control over engineered CAR T cell function - Fraessle, Simon P.; Tschulik, Claudia; Effenberger, Manuel; Cletiu, Vlad; Gerget, Maria; Schober, Kilian; Busch, Dirk H.; Germeroth, Lothar; Stemberger, Christian; Poltorak, Mateusz P. (Communications Biology, 2023)
CAR T cell therapy is a rapidly growing area of oncological treatments having a potential of becoming standard care for multiple indications. Coincidently, CRISPR/Cas gene-editing technology is entering next-generation CAR T cell product manufacturing with the promise of more precise and more controllable cell modification methodology. The intersection of these medical and molecular advancements creates an opportunity for completely new ways of designing engineered cells to help overcome current limitations of cell therapy. In this manuscript we present proof-of-concept data for an engineered feedback loop. We manufactured activation-inducible CAR T cells with the help of CRISPR-mediated targeted integration. This new type of engineered T cells expresses the CAR gene dependent on their activation status. This artifice opens new possibilities to regulate CAR T cell function both in vitro and in vivo. We believe that such a physiological control system can be a powerful addition to the currently available toolbox of next-generation CAR constructs.
CRIS-Team Scopus Importer:2024-11-19